(untitled) (Homoeopathy for All, 2023)
Black hairy tongue is a benign self-limiting disorder characterized by hypertrophy of the filiform papil lae of the tongue. In this condition a brownish-black discoloration of the papillae occurs.The etiology is still unclear but the condition is associ ated with numerous predisposing conditions. Homoeopathic medicine prescribed after proper casetaking and repertorization has shown ef fectiveness in treating black hairy tongue. A 45-year-old woman came with a complaint of blackish discol oration on tongue. A detailed case history was taken and after proper repertorization, the constitutional medicine was prescribed along with repeated follow-ups were taken at an interval of 15 days. The follow-ups of the patient showed remarkable improvement in her condition